Investigating Consumer Attention to Price in Travel Agency Advertisements through Eye Tracking Patterns - Mohsen Nazari; Roza Hendijani; Zeinab Mohammadi; Saeideh Esmaeili (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2021)
Eye tracking patterns will be used to explain how people's brain processes when faced with visual stimuli in travel agency advertising packages. The purpose of this study was to explore the effect of price points (discount formatting) and price visibility (Variable display location) on people's attention towards prices in social media campaigns. The research variables are the time to first fixation, fixation count at the price, visit duration, and visit count to the area of interest. The results of the experiment showed that discount formatting had an impact on fixation count, visit duration, and visit count on the price, and the presentation of discounts in the form of cash and gifts attracted more attention. Also the price displayed at the top left got more attention.